2022
DOI: 10.1155/2022/7099856
|View full text |Cite
|
Sign up to set email alerts
|

Structural Design of Handicrafts Based on Dynamic Simulation Technology

Abstract: In order to improve the effect of handicraft structure design, this study combines the dynamic simulation technology to build a handicraft structure design system and transmits data through dynamic simulation signals to improve the effectiveness of the interactive design of artworks. In order to provide a simpler and faster development process for interactive media applications, this study develops an interactive media art design system with a node-based visual programming model as the core processing logic. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The basic idea of play in early childhood education and the importance of digital technology in the teaching and learning process also has an influence on broader behavior when children play. It can be concluded that teachers can integrate digital technology into the process of early childhood play (Leung et al, 2019); (Meng & Liu, 2022;Radesky et al, 2022;Snyder, 2022;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The basic idea of play in early childhood education and the importance of digital technology in the teaching and learning process also has an influence on broader behavior when children play. It can be concluded that teachers can integrate digital technology into the process of early childhood play (Leung et al, 2019); (Meng & Liu, 2022;Radesky et al, 2022;Snyder, 2022;Zhang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%